Use of different proportions of red and blue LEDs to improve the growth of Lilium spp. - Flores Pérez, Silvia; Castillo-González, Ana María; Valdez-Aguilar, Luis Alonso; Avítia-García, Edilberto (Revista Mexicana de Ciencias Agrícolas, 2021)
The combination of red and blue light emitting diodes (LEDs) is an effective light source for plant growth and development. Several species of the genus Lilium are valued as cut flowers, but the information on the effect of the quality of light on their growth is still very scarce and it is necessary to determine the optimal light spectrum that allows obtaining desirable characteristics. The objective of this paper was to evaluate the growth of Lilium spp. ‘Corvara’ with LED lighting. The proportion of red and blue LED lights in each treatment was: 20:80 (R4B); 40:60 (2R3B); 60:40 (3R2B); 80:20 (4RB) and the control (W) with 100% white light. All treatments had a photosynthetically active radiation of 90 ±10 μmol m-2 s-1 during a photoperiod of 14 h. The work was conducted in Chapingo, Mexico in 2019 and 2020. The results showed that, the lowest number of days to harvest maturity (91 days) and the plants of lower height (83 cm) occurred with the illumination of treatment 2R3B. Regarding the control, increases were achieved in the following variables: with treatment R4B, leaf area 26% and tepal color 13% in the variable Chroma; with 3R2B, vase life 6%, with 4RB, plant height 21%, flower diameter 5% and the number of days to maturity was 16. It is concluded that the proportion of red and blue light modifies the growth and development of Lilium spp. ‘Corvara’ plants.